Pendugaan tingkat bahaya erosi pada hutan dan lahan Kopi Arabika (Coffea arabica) di Kecamatan Sibolangit - Devisna Situngkir; Jamilah; Posma Marbun (Talenta Publisher, 2018)
Vegetation is one of the factors affecting the actual erosion of a land. The changes in forest land use patterns into coffee lands can increase the erosion hazard. The aim of this research was to get information about erosion hazard level in forest and coffee arabica lands in Sibolangit Sub District by using USLE (Universal Soil Loss Equation) method. The Research was conducted in January-July 2017 in Sibolangit District at three villages ie Negeri Suah, Bukum and Cinta Rakyat. In this research, were 6 samples in Arabica coffee field sample (1, 2 and 3) and in Forest sample (1, 2 and 3). The research was conducted by using survey method and continued with soil erosion calculation by USLE (Universal Soil Loss Equation) prediction equation. The results showed that the value of erosion in the coffee arabica land in Cinta Rakyat Village on the slope of 60% was 432,87 ton.ha-1.year-1 (very high). The highest erosion hazard level in Bukum Village on the slope of 25% was 88,144 ton.ha-1.year-1 and the highest erosion hazard level in the Negeri Suah Village on the slope of 46% was 193,083 ton.ha-1.year-1. The value of erosion in the area forest in the Cinta Rakyat Forest on the slope 58% was 1,087 ton.ha-1.year-1with lowest erosion hazard. The lowest erosion hazard level in the Bukum Forest on the slope of 21% was 0,190 ton.ha-1.year-1and the lowest erosion hazard level in the Negeri Suah Forest on the slope of 36 % was 0,309 ton.ha-1.year-1.